Preliminary inventory of non-wood resources in Ayer Hitam Forest Reserve, Selangor - Yaman, Amat Ramsa; Sahri, Mohd Hamami; Kamardin, Mohamad; Ramli, Noramzaidy (Universiti Putra Malaysia Press, 2001)
An inventory on non-wood taxa in Compartment 12 of the Ayer Hitam Forest Reserve recorded four species of bamboo and seven species of palms. The bamboo species are Bambusa vulgaris, Gigantochloa scortechinii, Schizostachyum zollingeri and Bambusa heterostachya. The palms species are Eugeissonia tristis, Oncospenna horridum, Oncospenna tigillarium, Arenga obtusifolia, Livistona rotundifolia, Licuala glabra and Salacca 1.lllacca. This forest is considerably rich in palms but poor with bamboos.